Pola, tren, dan perbedaan praktik menyusui di Indonesia: analisis deskriptif peran modernisasi dan budaya tradisional dari data Survei Demografi Kesehatan Indonesia 2007 - Siswanto Agus Wilopo (Jurnal Gizi Klinik Indonesia, 2009)
Background : A modernization can lead to the adoption of western behavior while cultural values can also prevails, resulting in rejection of certain aspects of modernity. The question is how such conflicting forces affect breastfeeding practices in Indonesian women. Objective : This study examined modern and traditional factors that may affect pattern, trends and differentials of breastfeeding in Indonesia. Methods : The study based on data from Indonesian Demographic Health Survey (IDHS) conducted in 2007. There were 32.895 women or 19.939 children born after January 2002 and contributed to this information. We used duration of breastfeeding as dependent variables which based on information pertained to the last two children of respondent. The variable was calculated as the number of months that the mother reports having breastfed the child. The early use of supplementary food for children and the use of health services were examined to represent cultural values and modernity respectively. Socio-economic and demographic variables were considered important variables for breastfeeding practices. Kaplan Meier graphs were employed for the analysis of pattern, trends, and differentials of breastfeeding.Result : In Indonesia, the duration of breastfeeding varied between provinces. There was a trend of shortening of duration breastfeding about two months during 5 years period. Factors associated with modernity were significant determinant in shortening breastfeeding practice. These included: type of residence (urban or rual), level of education, prenatal care, previous or ever use of contraceptives, delivery at the hospital, and the use of an infant formula. Conclusion : Factors associated with modernity were significant in terms of early termination of breastfeeding. Traditional factors associated with breastfeeding practice did not show significant roles in maintaining the breastfeeding practice. We recommend to use a social enginering to include breastfeeding practice as a part of modern health practices.